Family Ceremonies as a Constraint on Informal Sector Investment: The Case of Sénégal - John Bennett; Stephanie Levy (Institute of Labor Economics (IZA), 2018)
We analyze how intermittent large expenditures on family ceremonies may affect an entrepreneur's investment decision in an informal enterprise. Our hypothesis is that the barrier between family and enterprise is thin and permeable. We test this hypothesis using a survey from Sénégal that combines informal sector and household data. We estimate a measure of exposure to spending on births, weddings and funerals, and show this has a significant negative relationship with the decision to invest and the amount of investment. These results are robust to changes in specifications of the determinants of investment, controlling for both enterprise- and family-related variables.
Keywords: O17; D13; O12; 330; informality; investment behaviour; family ceremonies